Loneliness-based impaired reward system pathway: Theoretical and clinical analysis and application. (April 2021) - Wilkialis, Linas; Rodrigues, Nelson; Majeed, Amna; Lee, Yena; Lipsitz, Orly; Gill, Hartej; Tamura, Jocelyn; Nasri, Flora; Lui, Leanna M.W.; Siegel, Ashley; Mansur, Rodrigo B.; Rosenblat, Joshua D.; et al.
Highlights: The reward system is an influencing factor in the loneliness-depression pathway Brain inflammation leads to insulin resistance, which impairs the reward system 'Reward' depression presents comorbid symptoms (with other mental disorders) Early childhood factors play a role in the formulation of an impaired reward system Consecutive losses will trigger similar defensive response from earlier childhood Abstract: Loneliness is a key determinant in the etiology of mental health disorders such as depression and has profound impacts on health, quality of life, and economic productivity. This narrative review uses extant neurobiology and evolutionary literature to propose a construct through which loneliness may induce depression in adulthood via the reward system (including symptom and treatment aspects). Early childhood (distal) factors were found to be important in influencing adult (proximal) factors, which lead to the formulation of the construct. Due to the heterogenous and comorbid nature of depression, a new subtype known as 'reward depression' was distinguished along with distinct symptoms to aid practitioners when assessing patient treatment options. Furthermore, an evolutionary perspective was applied to the current impaired reward construct to discuss how the ancestral purpose and environment (in terms of reward) clashes with the modern one. Finally, theoretical treatment and prevention ideas were examined and discussed, leading into future work that needs to build upon and confirm the outlined construct.